Becoming T.S. Eliot : the rhetoric of voice and audience in Inventions of the March hare - Stayer, Jayme (Johns Hopkins University Press, 2021)
Focusing on the period from 1909 to 1915, this incisive portrait of Eliot as a budding writer is as much a study of Eliot himself as it is a study of how a writer hones his voice.